2017
DOI: 10.18632/oncotarget.20749
|View full text |Cite
|
Sign up to set email alerts
|

Decreased TOB1 expression and increased phosphorylation of nuclear TOB1 promotes gastric cancer

Abstract: TOB1, a member of the BTG/TOB protein family, inhibits tumor cell proliferation. We previously observed down-regulation and phosphorylation of TOB1 in gastric cancer (GC). Here, we examined the subcellular distribution and clinical significance of TOB1 expression and phosphorylation in GC. Immunohistochemical analysis of 341 primary GC and corresponding normal gastric tissue samples demonstrated that nuclear TOB1 expression was lower in GC than normal tissue (80.4% vs. 92.4%), and decreased nuclear TOB1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Another way of transmitting ERK-dependent nuclear activity is by inhibition of tumor suppressor proteins, and example for such mechanism is Tob [ 78 ]. This transcriptional suppressor demonstrates antiproliferative function by binding to transcription factors in the nucleus and suppressing the expression of cyclin D1 and other regulatory genes [ 79 , 80 ]. Importantly, ERK phosphorylates Tob in the nucleus on Sers 152, 154, and 164 and these phosphorylations inhibit Tob activation and may support carcinogenesis [ 81 ].…”
Section: Nuclear Substrates Of Erk In Cancer Development and Maintmentioning
confidence: 99%
“…Another way of transmitting ERK-dependent nuclear activity is by inhibition of tumor suppressor proteins, and example for such mechanism is Tob [ 78 ]. This transcriptional suppressor demonstrates antiproliferative function by binding to transcription factors in the nucleus and suppressing the expression of cyclin D1 and other regulatory genes [ 79 , 80 ]. Importantly, ERK phosphorylates Tob in the nucleus on Sers 152, 154, and 164 and these phosphorylations inhibit Tob activation and may support carcinogenesis [ 81 ].…”
Section: Nuclear Substrates Of Erk In Cancer Development and Maintmentioning
confidence: 99%
“…Our results showed that CXCR4 , DDIT4 , and TOB1 were the highest before occluder treatment and downregulated after treatment with both PLLA and metal device. Previous studies demonstrated that DDIT4 regulates cell growth, proliferation, and survival by inhibiting the activity of mammalian mTORC1 targets ( Wang et al, 2015 ), while TOB1 , as an anti-proliferative gene, can regulate cell growth and differentiation and has a migratory role ( Liu et al, 2015 ; Guan et al, 2017 ; Shangguan et al, 2019 ). Finally, we also confirmed that CXCR4 is a candidate gene responsible for cardiac congenital pathologies in human as previously suggested in mouse studies ( Escot et al, 2013 ; Wang et al, 2014 ; Zhong and Rajagopalan, 2015 ; Page et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we identified that decreased TOB1 expression and increased nuclear phosphorylated TOB1 were associated with aggressive tumor behavior and a poor prognosis in intestinal type GC. Additionally, TOB1 nuclear retention is critical for its anti-proliferative activity in vitro 16 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, an increasing number of researches focus on the role of TOB1 in gastric cancerogenesis, which including the localization and expression of the gene 13 - 15 , the mechanisms of inactivation, tumor suppressor involving the participating pathways, and its effect in the cell cycle, etc. 16 , 28 , 38 . A new study reported that TOB1 gene was contribute to estrogen-independent breast cancer and the interaction effects between TOB1 gene with AKT/mTOR survival signaling 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation